The association between tumor burden and severe immune-related adverse events in non-small cell lung cancer patients responding to immune-checkpoint inhibitor treatment. (April 2019) - Sakata, Yoshihiko; Kawamura, Kodai; Ichikado, Kazuya; Shingu, Naoki; Yasuda, Yuko; Eguchi, Yoshitomo; Anan, Keisuke; Hisanaga, Junpei; Nitawaki, Tatsuya; Iio, Miwa; Sekido, Yuko; Nakano, Aiko; et al.
Highlights: Little is known about treatment responders likely to develop severe irAEs. This study evaluated the association of tumor burden with severe irAEs in NSCLC. Only patients responding to ICI treatment were included. High tumor burden was a risk factor of severe irAE in patients responding to ICI. Abstract: Objectives: The use of immune checkpoint inhibitors (ICIs) for advanced non-small cell lung cancer (NSCLC) has demonstrated survival benefits, although some treatment responders (defined as patients with non-progressive disease) are forced to discontinue treatment because of severe immune-related adverse events (irAEs). An association between treatment efficacy and irAEs has been reported. However, it is unclear which treatment responders are likely to develop severe irAEs. We aimed to examine risk factors for ICI-related severe irAEs in patients with NSCLC. Materials and methods: Between February 2016 and October 2018, we retrospectively evaluated 42 patients with NSCLC at our institution who responded to ICI treatment. Tumor burden was measured as the sum of the unidimensional diameters of up to five target lesions, according to the Response Evaluation Criteria in Solid Tumors version 1.1. Results: ICIs were discontinued in 15 of 42 treatment responders because of severe irAEs. Tumor burden was a significant independent predictor of severe irAEs (p = 0.03). The odds ratio of severe irAEs and tumor burden over 90 mm was 8.62 (95% confidence interval = 1.96–37.9, p = 0.004). Conclusion: A high tumor burden was a risk factor for severe irAEs in patients with NSCLC who responded to ICI treatment.